Respuesta :

Answer:

x = -0.683 (3dp)

x = -7.317 (3dp)

Step-by-step explanation:

Step 1: Apply the quadratic formula

(-b±([tex]\sqrt{b^{2}-4ac}[/tex])) / 2a

a = 1 (x²)

b = 8 (8x)

c = 5 (5)

(-8±([tex]\sqrt{8^{2}-4 x 1 x 5}[/tex])) / 2 x 1

Step 2: Simplify

(-8±([tex]\sqrt{44}[/tex])) / 2

Step 3: Solve

You need to replace the ± with first a + and then a -.

(-8+([tex]\sqrt{44}[/tex])) / 2 = -0.683 (3dp) = x

(-8-([tex]\sqrt{44}[/tex])) / 2 = -7.317 (3dp) = x

Hope this helps!

ACCESS MORE